The Influence of Social Media Marketing and Brand Image on Consumer Loyalty with Customer Engagement as a Mediating Variable in Franchise Coffee Shops - Dwi Adeningsih Saputri Elhuria; Jeni Kamase; Muhammad Akhsan Tenrisau (Journal Social Society, 2026)
The urgency of this study is to examine how social media marketing and brand image influence consumer loyalty through customer engagement, enabling franchise coffee shops to strengthen customer retention and remain competitive in an increasingly crowded market. This study investigates the influence of social media marketing and brand image on consumer loyalty, with customer engagement as a mediating variable, in coffee shops in Makassar City. The rapid growth of digital marketing strategies has intensified competition in the coffee shop industry, making it essential to understand how marketing activities and brand perception drive long-term customer relationships. This research employs a quantitative approach using primary data collected through structured questionnaires distributed to 200 respondents selected through purposive sampling. The study focuses on three coffee shops in Makassar City: Vaan In Sky, Toko Kopi Oma, and Cuci Mulut. Data analysis was conducted using descriptive statistics and Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings reveal that social media marketing and brand image have a positive and significant effect on customer engagement. Furthermore, customer engagement significantly influences consumer loyalty. The results also indicate that social media marketing and brand image directly affect consumer loyalty in a positive and significant manner. Importantly, customer engagement serves as a partial mediating variable, strengthening the relationship between social media marketing, brand image, and consumer loyalty. The implication of this study is that coffee shop managers should prioritize interactive and consistent social media strategies alongside strengthening brand identity to enhance customer engagement, which in turn leads to higher consumer loyalty. This study contributes to the literature on digital marketing and consumer behavior, particularly in the context of the growing coffee shop industry in Indonesia.